The more academic burnout students got, the more problematic mobile phone use they suffered? A meta-analysis of mainland Chinese adolescents and young adults - Li, Shunyu; Xu, Mengmeng; Zhang, Yuxuan; Wang, Xiaotong (Frontiers in Psychology, 2023)
Introduction In recent years, the relationship between academic burnout (AB) and problematic mobile phone use (PMPU) has become the hot issue of scholars, and a lot of related research has been carried out, but the results are different. Most studies showed that there was a significant positive correlation between AB and PMPU. However, some studies showed that the relationship between AB and PMPU was not significant. While this study aimed at exploring the relationship between AB and PMPU, as well as the influence of some moderating factors (region, age, gender, publication year, the measurement instrument) on them. Methods According to the searching process for studies of PRISMA, we searched the related studies on AB and PMPU in Mainland China from January 2012 to November 2022 from CNKI, Wanfang Data, Chongqing VIP Information Co., Ltd. (VIP), Baidu scholar, ProQuest dissertations, Taylor & Francis, Springer, Web of Science, Google Scholar, EBSCO and PsyclNFO. Eventually, 50 studies were included in the meta-analysis, involving 38,488 subjects, with the sample size ranging from 193 to 2,260. CMA 3.0 was used to analyze the overall effect and test the moderating effect. Results The result shows that the relationship between AB and PMPU can be considered as a moderate correlation (r = 0.414, 95%CI [0.384, 0.443]), and moderator analysis shows that the relationship between AB and PMPU was moderated by the measurement instrument and publication year. Discussion Specifically, when the Mobile Phone Addiction Tendency Scale and the Smartphone Addiction Scale for College Students were used as PMPU measurement tools, the correlation coefficients between AB and PMPU were higher. When the publication year was used as a moderating variable, the relationship between AB and PMPU increased over the years. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022347277, identifier PROSPERO CRD42022347277.